Legal Realism Roscoe Pound dalam Sidang Pleno MA 2019 tentang Nafkah Madhiyah Anak - Mafiah, Yeni (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
The child’s madhiyah income is past income for the child which was not paid for by the father when the father and mother were still in a marriage bond. And the maintenance of this child’s madhiyah is usually required to be paid at the time or after a divorce occurs. This study aims to determine the relevance of Roscoe Pound’s theory of legal realism in the 2019 Supreme Court Plenary Session on the maintenance of madhiyah children. The research method uses a type of library research or library research, with a qualitative approach. The result of his research is that Roscoe Pound’s legal realism thinking prioritizes practical goals. According to Pound, legal practice and its impact on society are more important than the legal texts themselves. Supreme Court Decision No. 608/K/AG/2003 concerning refusal to provide for a child’s madhiyah is considered to be injurious to the value of justice. Until finally the plenary session of the Supreme Court chamber in 2019 decided that a child’s madhiyah maintenance could be brought to court. From the results of the research above, there is a correlation between Roscoe Pound’s legal realism theory and the 2019 Supreme Court chamber plenary session regarding the maintenance of madhiyah children. This research is expected to open up philosophical insights into a legal decision. Keywords: Legal Realism, Child Madhiyah Support, Plenary Session of the Supreme Court